When a hundred flowers blossom: (re)assembling the Chinese orchestra in contemporary Malaysia as a cultural ecosystem - Elynn, Tan (2025)
The Chinese orchestra in Malaysia is a significant cultural emblem that represents the Malaysian Chinese identity, yet it remains understudied and widely misunderstood, generally construed through antiquated historical and descriptive perspectives that decontextualizes its existing struggles and adaptiveness to contemporaneity. Cultural ecology concepts from Titon (2020) and ecological metaphors from Deleuze and Guattari (1987) are adopted to frame the Malaysian Chinese orchestra as a complex and interdependent cultural ecosystem that is resilient and adaptable to environmental changes. Mainly, this study refreshes the perspectives of current and new audiences of the Chinese orchestra in Malaysia through a reassembling of its dynamics, constructs, and operations in the 2020s. Research methodology consists of experimentation and expert interviews, supported by the author’s own autoethnographic observations as a cultural insider. The gaoyin ruan modification experiment aims to enhance its musical versatility, and Experiment Ensembles are conducted to study organization, performativity, space, resilience, and musical hybridity. Collected data are coded and visualized for a balanced quantitative and qualitative analysis. A theoretical network is used to map opportunities and challenges through rhizomatic writing, along topics of spaces, performativity, identity, multiculturalism, musical hybridity, digitalization, and cultural sustainability. Findings reveal the Chinese orchestra’s roles and values in the search for a Malaysian Chinese identity in a multicultural country, while examining its resilience and adaptive management plans towards disruptions and socio-cultural shifts. There are conscious and subconscious efforts towards sustainability for both the cultural ecosystem and the natural environment. Cross-cultural and cross-disciplinary collaborations are budding to advance the value of huayue in creative practices and musical hybridity, fostering interculturalism. Finally, the proposed Cultural Sustainability Web is a model to outline sustainable future trajectories for traditional cultures and provide strategies for social cohesion, that can generate a long-term impact on the Malaysian Chinese orchestra cultural ecosystem.